2021
DOI: 10.31234/osf.io/hn26a
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing the overarching continuum theory: Data-driven phenotypic clustering of children with ASD or ADHD

Abstract: The clinical validity of the distinction between ADHD and ASD is a longstanding discussion. Recent advances in the realm of data-driven analytic techniques now enable us to formally investigate theories aiming to explain the frequent co-occurrence of these neurodevelopmental conditions. In this study, we probe different theoretical positions by means of a pre-registered integrative approach of novel classification, subgrouping and taxometric techniques in a representative sample (N=434) and replicate the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…We found that ADHD and autistic traits formed two distinct factors as hypothesised. Next, and consistent with existing literature (e.g., Deserno et al., 2022; Posner et al., 2020), the distribution of CPRS ratings in both our samples supported the description of ADHD as a continuum extending from neurotypical profiles. We were also able to successfully replicate a 2‐factor, 2‐class FMM‐3 model in two independent samples based on responses to the AQ and CPRS.…”
Section: Discussionsupporting
confidence: 91%
“…We found that ADHD and autistic traits formed two distinct factors as hypothesised. Next, and consistent with existing literature (e.g., Deserno et al., 2022; Posner et al., 2020), the distribution of CPRS ratings in both our samples supported the description of ADHD as a continuum extending from neurotypical profiles. We were also able to successfully replicate a 2‐factor, 2‐class FMM‐3 model in two independent samples based on responses to the AQ and CPRS.…”
Section: Discussionsupporting
confidence: 91%